IFCEE 2021 Geoenvironmental Engineering, Geomaterial Modeling, Transportation Geotechnics, and Case Histories - El Mohtar, Chadi; Kulesza, Stacey; Baser, Tugce; Venezia, Michael D. (American Society of Civil Engineers, 2021)
Selected papers from the International Foundations Congress and Equipment Expo 2021, held in Dallas, Texas, May 10-14, 2021. Sponsored by the International Association of Foundation Drilling (ADSC), the Deep Foundations Institute (DFI), the Pile Driving Contractors Association (PDCA), and the Geo-Institute of ASCE.This Geotechnical Special Publication contains 39 peer-reviewed papers on applied geophysics for infrastructure, solutions for stabilizing historical structures, and case histories from around the world.Topics include: soil properties and modeling; geoenvironmental engineering; transportation geotechnics; and case histories.GSP 326 will be of interest to engineering practitioners, researchers, geotechnologists, contractors, and equipment manufacturers and suppliers in the deep foundation industry.
Keywords: Geotechnical engineering -- Mathematical models.; Transportation engineering -- Congresses.; elektronické knihy; electronic books